The Structure of the Barley Husk Influences Its Resistance to Mechanical Stress - Grant, Kathryn R.; Brennan, Maree; Hoad, Stephen P. (Frontiers in Plant Science, 2021)
This paper explores the links between genotype, plant development, plant structure and plant material properties. The barley husk has two organs, the lemma and the palea, which protect the grain. When the husk is exposed to mechanical stress, such as during harvesting, it can be damaged or detached. This is known as grain skinning, which is detrimental to grain quality and has a significant economic impact on industry. This study focused on the lemma, the husk organ which is most susceptible to grain skinning. This study tested three hypotheses: (1) genotype and plant development determine lemma structure, (2) lemma structure influences the material properties of the lemma, and (3) the material properties of the lemma determine grain skinning risk. The effect of genotype was investigated by using plant material from four malting barley varieties: two with a high risk of grain skinning, two with a low risk. Plant material was assessed at two stages of plant development (anthesis, GS 65; grain filling, GS 77). Structure was assessed using light microscopy to measure three physiological features: thickness, vasculature and cell area. Material properties were approximated using a controlled impact assay and by analysing fragmentation behaviour. Genotype had a significant effect on lemma structure and material properties from anthesis. This indicates that differences between genotypes were established during floral development. The lemma was significantly thinner in high risk genotypes, compared to low risk genotypes. Consequently, in high risk genotypes, the lemma was significantly more likely to fragment. This indicates a relationship between reduced lemma thickness and increased fragmentation. Traditionally, a thin husk has been considered beneficial for malting quality, due to an association with malt extract. However, this study finds a thin lemma is less resistant to mechanical stress. This may explain the differences in grain skinning risk in the genotypes studied.